Physiological and biochemical responses of barley to application of bio-fertilizers and nano iron oxide under salinity stress in greenhouse - Dadashzadeh, Siyamak; Shariff, Raouf Seyed; Farzaneh, Salim (Bangladesh Journal of Botany, 2018)
To study the effects of bio-fertilizers and nano iron oxide on some physiological and biochemical traits of barley under salinity stress, a factorial experiment was conducted based on RCBD with three replications under greenhouse condition. Factors in the study, included four levels of salinity, four levels of nano iron oxide use and four preparations of bio-fertilizer application. Increasing salinity in the soil decreased chlorophyll content, quantum yield, relative water content and grain yield, whereas soluble sugars, proline content, electrical conductivity and the activities of catalase, peroxidase and polyphenol oxidase enzymes increased. Inoculation of plants with bio-fertilizers and nano iron oxide application improved these traits (except electrical conductivity) under salinity as well as normal conditions. Results showed that application of Azospirillum and mycorrhiza and 0.9 g/l nano iron oxide (B3Fe3) increased about 15.45% from grain yield in comparison with B4Fe4 under the highest salinity level. Based on the results, it seems that bio-fertilizers and nano iron oxide application can be useful in alleviating salinity stress in barley.